Porous carbon negative electrode material, preparation method thereof and lithium ion battery
The synthesis of porous carbon negative electrode materials through eutectic solvents has solved the problem of low efficiency of starch-based hard carbon negative electrode materials for the first time, and the specific surface area and lithium storage performance have been improved, and the electrochemical performance has been improved.
Patent Information
- Application Number
- CN202510141104.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2045-02-08
AI Technical Summary
In the prior art, the first-time efficiency of starch-based hard carbon negative electrode materials is low and cannot effectively exert their lithium storage ability.
Porous carbon negative electrode material is synthesized by eutectic solvents, destroying hydrogen bonds between starch molecules and within molecules, dispersing starch homogeneously, and porous carbon material is achieved through the gas generated during calcination, improving specific surface area and lithium storage performance.
The specific surface area and lithium storage performance of carbon anode materials are improved, the first-time efficiency is enhanced, and the porous structure is more uniform, which is conducive to the improvement of electrochemical performance.
Smart Images

Figure CS0YZ77ZU8QZNVXXMOQANSP3HQ8Q3MPNLLMOJXNA
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a porous carbon negative electrode material and a preparation method thereof, and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are currently important energy storage devices. Due to their advantages of high energy density and long cycle life, they have been widely used in smart phones, portable appliances, medical electronics, power tools, power vehicles and other fields in recent years.
[0003] Among them, the negative electrode material is an important component of lithium-ion batteries and one of the important factors that determine the comprehensive performance of lithium-ion batteries. The negative electrode materials of lithium batteries are generally graphite, amorphous carbon, etc., especially hard carbon in amorphous carbon. Because of its many nanopores, its lithium storage capacity is generally higher than that of graphite materials. In recent years, it has become a research hotspot for negative electrode materials.
[0004] The raw materials for the common industrial preparation of hard carbon negative electrode materials are mainly non-renewable fossil resources such as coal, resin and asphalt. The main preparation methods include pyrolysis method, emulsion method, etc. These methods not only have complex process conditions or processes, but are also not conducive to environmental protection. Starch is a typical representative of polysaccharides. It is a renewable natural carbon source with a wide range of sources and low prices. It is an important raw material for the preparation of carbon materials. However, due to the special structure of starch, the initial efficiency of starch-based hard carbon negative electrode materials prepared with starch as the carbon source is low, and its lithium storage capacity cannot be brought into play.
[0005] In view of this, how to improve the initial efficiency of starch-based hard carbon negative electrode materials is a technical problem that needs to be solved urgently. Summary of the invention
[0006] In order to solve the problem of low first efficiency of starch-based hard carbon negative electrode materials in the prior art, the present invention provides a method for preparing a porous carbon negative electrode material. The preparation method synthesizes the porous carbon negative electrode material through a low eutectic solvent, improves the specific surface area and lithium storage performance of the carbon negative electrode material, and solves the problem of low first efficiency of amorphous carbon negative electrode materials in the prior art.
[0007] The technical solution adopted by the present invention to solve its technical problem is: A method for preparing a porous carbon negative electrode material comprises the following steps: mixing starch and a low eutectic solvent at 60-80°C to obtain a precursor; calcining the precursor at 350-550°C and 750-950°C in an inert atmosphere, and then grinding to obtain a porous carbon negative electrode material.
[0008] Optionally, the mass ratio of the starch to the low eutectic solvent is (0.8-1.5):1.
[0009] Optionally, the low eutectic solvent is a hydrogen bond donor-choline halide-lithium halide.
[0010] Optionally, the hydrogen bond donor-choline halide-lithium halide is obtained by mixing a hydrogen bond donor, a choline halide and a lithium halide at 70-90°C.
[0011] Optionally, the molar ratio of the hydrogen bond donor, the choline halide and the lithium halide is 1:2:1.
[0012] Optionally, the hydrogen bond donor is selected from at least one of oxalic acid and glycerol.
[0013] Optionally, the choline halide is selected from at least one of choline fluoride, choline chloride and choline bromide.
[0014] Optionally, the lithium halide is selected from at least one of lithium fluoride, lithium chloride and lithium bromide.
[0015] Another object of the present invention is to provide a porous carbon negative electrode material, which is prepared by the method for preparing the porous carbon negative electrode material as described above.
[0016] Another object of the present invention is to provide a lithium ion battery comprising the porous carbon negative electrode material as described above.
[0017] The beneficial effects of the present invention are: The method for preparing the porous carbon negative electrode material provided by the present invention, by introducing a low eutectic solvent, on the one hand destroys the hydrogen bonds between and within starch molecules, changes the arrangement of starch molecules from tightly ordered to scattered and disordered, homogeneously disperses the starch, and prevents starch agglomeration; on the other hand, the gas generated during the calcination of the low eutectic solvent is used to realize the porosity of the carbon material, thereby increasing the specific surface area and lithium storage performance of the carbon negative electrode material and improving the initial efficiency. DETAILED DESCRIPTION
[0018] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.
[0019] At present, the first efficiency of starch-based hard carbon negative electrode materials is usually improved by the porosification method; the common porous starch preparation process is to use amylase to corrode starch particles, starting from the amorphous area of the starch particles, corroding holes from the outside to the inside, resulting in irregular pits or even holes on the starch surface. This enzymatic method of preparing porous starch, when a small dose of enzyme is used, only corrodes pits on the surface of starch particles, and the corroded pits are often the amorphous area of starch, and the distribution uniformity is poor, which has limited effect on improving the electrochemical performance of negative electrode materials.
[0020] In order to solve the problem of low initial efficiency of starch-based hard carbon negative electrode materials in the prior art, the present invention provides a method for preparing a porous carbon negative electrode material, which comprises the following steps: mixing starch with a low eutectic solvent at 60-80°C, preferably at 65°C, to obtain a precursor; calcining the precursor at 350-550°C and 750-950°C in an inert atmosphere, preferably at 350°C and 850°C, and then grinding to obtain a porous carbon negative electrode material.
[0021] Starch is usually a mixture of amylopectin and amylose, and is a highly crystalline substance. There are a large number of hydrogen bonds between and within the molecules, which makes starch difficult to dissolve in water. The present invention mixes starch with a low eutectic solvent at 60-80°C, wherein the low eutectic solvent serves as a gelatinization solvent for starch, can homogeneously disperse the starch, dominate the "gelatinization" process of starch, and play a "depolymerization" role on the starch to prevent starch agglomeration; then calcination is performed, and the gas generated during the calcination of the low eutectic solvent is used to corrode and form pores to obtain a porous carbon material, thereby increasing the specific surface area and lithium storage performance of the carbon negative electrode material and improving the initial efficiency.
[0022] The method for preparing the porous carbon negative electrode material provided by the present invention, by introducing a low eutectic solvent, on the one hand destroys the hydrogen bonds between and within starch molecules, changes the arrangement of starch molecules from tightly ordered to scattered and disordered, homogeneously disperses the starch, and prevents starch agglomeration; on the other hand, the gas generated during the calcination of the low eutectic solvent is used to realize the porosity of the carbon material, thereby increasing the specific surface area and lithium storage performance of the carbon negative electrode material and improving the initial efficiency.
[0023] Compared with the method in the prior art of preparing porous starch by corroding starch granules with amylase and then further preparing porous starch-based negative electrode materials, the negative electrode material prepared in the present invention is first gelatinized by a low eutectic solvent, and then the carbon material is made porous by the gas generated by the low eutectic solvent during the calcination process. Therefore, in the carbon negative electrode material provided by the present invention, the porous structure is generated from the inside of the carbon material to the outside, and the porous distribution is more uniform, which is more conducive to the improvement of the electrochemical performance of the negative electrode material.
[0024] In order to take into account both the gram capacity and the initial efficiency of the carbon negative electrode material, the present invention preferably has a mass ratio of starch to the low eutectic solvent of (0.8-1.5):1, and further preferably has a mass ratio of starch to the low eutectic solvent of 1:1.
[0025] In order to ensure the electrochemical performance of the porous carbon negative electrode material, the present invention preferably uses the low eutectic solvent as a hydrogen bond donor - choline halide - lithium halide.
[0026] Among them, the hydrogen bond donor in the low eutectic solvent can combine with the precursor, i.e. starch, through hydrogen bonds, so that the low eutectic solvent is not easily washed away by deionized water, and can effectively inhibit the agglomeration of starch particles in the subsequent calcination process, which is beneficial to the porosity of carbon materials; the gas generated after the carbonization of choline halide is acidic components such as nitrogen oxides, hydrohalic acid, carbon dioxide and carbon monoxide, thereby producing a corrosion pore-forming effect, thereby improving the specific surface area and lithium storage performance of the carbon negative electrode material; and the carbon dioxide gas generated by the thermal decomposition of the hydrogen bond donor in the hydrogen bond donor-choline halide-lithium halide will further benefit the porosity of carbon materials; the lithium halide in the low eutectic solvent can be simultaneously embedded in the micropores of porous carbon during the pore-forming process, playing a role in lithium supplementation, which is beneficial to the formation of SEI film.
[0027] The hydrogen bond donor-choline halide-lithium halide of the present invention is preferably obtained by mixing a hydrogen bond donor, a choline halide and a lithium halide at 70-90°C, and is further preferably obtained by mixing a hydrogen bond donor, a choline halide and a lithium halide at 80°C.
[0028] Specifically, the molar ratio of the hydrogen bond donor, the choline halide and the lithium halide in the deep eutectic solvent is preferably 1:2:1.
[0029] In order to ensure the initial efficiency of the porous carbon negative electrode material, the present invention preferably selects the hydrogen bond donor from at least one of oxalic acid and glycerol; and preferably selects the choline halide from at least one of choline fluoride, choline chloride and choline bromide.
[0030] To facilitate the formation of the SEI film, the present invention preferably uses at least one of lithium halide selected from lithium fluoride, lithium chloride and lithium bromide.
[0031] The preferred starch of the present invention is at least one selected from cereal starch, potato starch and bean starch.
[0032] Specifically, the method for preparing the porous carbon negative electrode material in the present invention can be carried out according to the following process: S1: First, a hydrogen bond donor, a choline halide, and a lithium halide are stirred in a stirrer at a molar ratio of 1:2:1 at 70-90° C. for 3 h-5 h to obtain a low eutectic solvent of a hydrogen bond donor-choline halide-lithium halide; S2: Weigh starch and a low eutectic solvent in a mass ratio of (0.8-1.5):1, stir them in a stirrer at 60-80°C for 3h-5h, and then ultrasonicate the resulting mixture for 1-2h to obtain a precursor; S3: heating the precursor to 350-550°C in an inert gas atmosphere in a tube furnace, removing tar and gas, and heating it again to 750-950°C for 5-8 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0033] Another object of the present invention is to provide a porous carbon negative electrode material, which is prepared by the method for preparing the porous carbon negative electrode material as described above.
[0034] The porous carbon negative electrode material provided by the present invention introduces a low eutectic solvent during the preparation process, which, on the one hand, destroys the hydrogen bonds between and within starch molecules, changes the arrangement of starch molecules from tightly ordered to scattered and disordered, homogeneously disperses the starch, and prevents starch agglomeration; on the other hand, the gas generated during the calcination of the low eutectic solvent is used to realize the porosity of the carbon material, thereby increasing the specific surface area and lithium storage performance of the carbon negative electrode material and improving the initial efficiency.
[0035] Another object of the present invention is to provide a lithium ion battery comprising the porous carbon negative electrode material as described above.
[0036] The lithium-ion battery provided by the present invention introduces a low eutectic solvent into the porous carbon negative electrode material during the preparation process, which, on the one hand, destroys the hydrogen bonds between and within starch molecules, changes the arrangement of starch molecules from tightly ordered to scattered and disordered, homogeneously disperses the starch, and prevents starch agglomeration; on the other hand, the gas generated during the calcination of the low eutectic solvent is used to realize the porosity of the carbon material, thereby increasing the specific surface area and lithium storage performance of the carbon negative electrode material and improving the initial efficiency.
[0037] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below.
[0038] Example 1 This embodiment provides a method for preparing a porous carbon negative electrode material, the preparation method comprising the following steps: S1: First, oxalic acid, choline chloride and lithium chloride were stirred in a stirrer at a molar ratio of 1:2:1 at 80°C for 5 h to obtain a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride; S2: Weigh corn starch and a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride in a mass ratio of 1:1, stir the mixture in a stirrer at 65° C. for 3 h, and then ultrasonicate the mixture for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas are removed, and the temperature is again raised to 850°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0039] Example 2 This embodiment provides a method for preparing a porous carbon negative electrode material, the preparation method comprising the following steps: S1: First, glycerol, choline fluoride and lithium fluoride were stirred in a stirrer at 80° C. for 4 h in a molar ratio of 1:2:1 to obtain a deep eutectic solvent of glycerol-choline fluoride-lithium fluoride; S2: wheat starch and a deep eutectic solvent of glycerol-choline fluoride-lithium fluoride were weighed in a mass ratio of 1:1, stirred in a stirrer at 65° C. for 4 h, and then the obtained mixture was sonicated for 1 h to obtain a precursor; S3: The precursor is heated to 450°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 6 hours, tar and gas are removed, and the temperature is again raised to 950°C, and the temperature is kept at this temperature for 8 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0040] Example 3 This embodiment provides a method for preparing a porous carbon negative electrode material, the preparation method comprising the following steps: S1: First, glycerol, choline bromide and lithium bromide were stirred in a stirrer at 80° C. for 3 h in a molar ratio of 1:2:1 to obtain a deep eutectic solvent of glycerol-choline bromide-lithium bromide; S2: Weigh potato starch and a low eutectic solvent of glycerol-choline bromide-lithium bromide in a mass ratio of 1:1, stir them in a stirrer at 65° C. for 4 h, and then ultrasonicate the resulting mixture for 2 h to obtain a precursor; S3: heating the precursor to 550°C in an argon protective atmosphere in a tube furnace, keeping the temperature for 5 hours, removing tar and gas, and heating it again to 850°C, keeping the temperature for 5-8 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0041] Example 4 This embodiment provides a method for preparing a porous carbon negative electrode material, the preparation method comprising the following steps: S1: First, oxalic acid, choline chloride and lithium chloride were stirred in a stirrer at 80° C. for 3 h in a molar ratio of 1:2:1 to obtain a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride; S2: wheat starch and a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride were weighed in a mass ratio of 1:1, stirred in a stirrer at 65° C. for 4 h, and then the obtained mixture was sonicated for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas are removed, and the temperature is again raised to 750°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0042] Example 5 This embodiment provides a method for preparing a porous carbon negative electrode material, the preparation method comprising the following steps: S1: First, oxalic acid, choline chloride and lithium chloride were stirred in a stirrer at a molar ratio of 1:2:1 at 80°C for 5 h to obtain a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride; S2: Weigh corn starch and a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride in a mass ratio of 0.8:1, stir the mixture in a stirrer at 65° C. for 3 h, and then ultrasonicate the mixture for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 8 hours, tar and gas are removed, and the temperature is again raised to 850°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0043] Example 6 This embodiment provides a method for preparing a porous carbon negative electrode material, the preparation method comprising the following steps: S1: First, oxalic acid, choline chloride and lithium chloride were stirred in a stirrer at a molar ratio of 1:2:1 at 80°C for 5 h to obtain a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride; S2: corn starch and a deep eutectic solvent of oxalic acid-choline chloride-lithium chloride were weighed in a mass ratio of 1.5:1, stirred in a stirrer at 65° C. for 3 h, and then ultrasonicated the resulting mixture for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas are removed, and the temperature is again raised to 850°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain the target product of the present invention, i.e., a porous carbon negative electrode material.
[0044] Comparative Example 1 This comparative example provides a method for preparing a negative electrode material, comprising the following steps: S1: The temperature of corn starch was raised to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas were removed, and the temperature was raised to 850°C again, and the temperature was kept at this temperature for 6 hours; S2: Grind the product of step S1 to obtain a negative electrode material.
[0045] Comparative Example 2 This comparative example provides a method for preparing a negative electrode material, comprising the following steps: S1: First, oxalic acid and choline chloride were stirred in a stirrer at 80° C. for 5 h in a molar ratio of 1:2 to obtain a deep eutectic solvent oxalic acid-choline chloride; S2: corn starch and a deep eutectic solvent oxalic acid-choline chloride were weighed in a mass ratio of 1:1, stirred in a stirrer at 65° C. for 3 h, and then the obtained mixture was sonicated for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas are removed, and the temperature is again raised to 850°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain a negative electrode material.
[0046] Comparative Example 3 This comparative example provides a method for preparing a negative electrode material, comprising the following steps: S1: First, choline chloride and lithium chloride are stirred in a stirrer at a molar ratio of 2:1 at 80°C for 5 hours to obtain a deep eutectic solvent of choline chloride-lithium chloride; S2: corn starch and a deep eutectic solvent of choline chloride-lithium chloride were weighed in a mass ratio of 1:1, stirred in a stirrer at 65° C. for 3 h, and then the obtained mixture was sonicated for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas are removed, and the temperature is again raised to 850°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain a negative electrode material.
[0047] Comparative Example 4 This comparative example provides a method for preparing a negative electrode material, comprising the following steps: S1: First, oxalic acid and lithium chloride were stirred in a stirrer at 80° C. for 5 h in a molar ratio of 1:1 to obtain a mixture of oxalic acid-lithium chloride; S2: Weigh corn starch and a mixture of oxalic acid and lithium chloride in a mass ratio of 1:1, stir them in a stirrer at 65° C. for 3 h, and then ultrasonicate the resulting mixture for 2 h to obtain a precursor; S3: The precursor is heated to 350°C in an argon protective atmosphere in a tube furnace, kept at this temperature for 7 hours, tar and gas are removed, and the temperature is again raised to 850°C, and the temperature is kept for 6 hours; S4: Grind the product of step S3 to obtain a negative electrode material.
[0048] The negative electrode materials prepared in the above-mentioned embodiments and comparative examples were prepared into button-type batteries by the button-type battery process and tested. The test results are shown in Table 1.
[0049] The preparation process of button cells is as follows: The negative electrode materials prepared in the above embodiments and comparative examples were respectively used as negative electrode active materials, and were uniformly mixed with polyvinylidene fluoride (PVDF) (dissolved in N-methylpyrrolidone) and conductive carbon black in a mass ratio of 90:5:5, coated into an electrode film, placed in a vacuum drying oven at 120°C for 12 hours, and rolled and punched to obtain a negative electrode sheet; a PP film was used as a button separator, and a metal lithium sheet was used as a counter electrode. The hard carbon negative electrode sheet obtained above was assembled into a 2430 button battery in a glove box, and its electrochemical performance was tested (test voltage (0-3) V, current 0.05C). The results are shown in Table 1; Table 1 It can be seen from the data in the above table that the negative electrode materials prepared in various embodiments of the present invention have relatively high gram capacity and excellent first efficiency.
[0050] The technical solution provided in Comparative Example 1 directly calcined the starch. Since the starch was severely agglomerated and could not be made porous, the gram capacity and the first efficiency of the prepared negative electrode material were significantly reduced.
[0051] In the technical solution provided in Comparative Example 2, no lithium halide is added to the low eutectic solvent. Although corrosion pore formation can be achieved during the calcination process, lithium replenishment cannot be performed simultaneously during the pore formation process. As a result, the prepared negative electrode material has a higher gram capacity but a lower initial efficiency.
[0052] The technical solution provided in Comparative Example 3 uses choline chloride and lithium chloride as low eutectic solvents. However, since the hydrogen bonds between starch molecules cannot be destroyed, starch agglomeration cannot be effectively alleviated, and the pores are insufficient, the first efficiency of the prepared negative electrode material is improved compared with that of Comparative Example 1, but the gram capacity and the first efficiency are significantly lower than those of Example 1.
[0053] The technical solution provided in Comparative Example 4 uses a mixture of oxalic acid and lithium chloride to replace the low eutectic solvent. Although oxalic acid is beneficial to porosity, due to the lack of choline chloride, lithium chloride has no effective connection, resulting in the prepared negative electrode material. Although the gram capacity is greatly improved compared with Comparative Example 1, the gram capacity and the first efficiency are significantly lower than those in Example 1 because lithium chloride cannot effectively remain in the pores.
[0054] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a porous carbon negative electrode material, characterized in that: The method comprises the following steps: mixing starch and a low eutectic solvent at 60-80° C. to obtain a precursor; calcining the precursor at 350-550° C. and 750-950° C. in an inert atmosphere, and then grinding the precursor to obtain a porous carbon negative electrode material.
2. The method for preparing the porous carbon negative electrode material according to claim 1, characterized in that: The mass ratio of the starch to the low eutectic solvent is (0.8-1.5):
1.
3. The method for preparing the porous carbon negative electrode material according to claim 1, characterized in that: The deep eutectic solvent is a hydrogen bond donor-choline halide-lithium halide.
4. The method for preparing the porous carbon negative electrode material according to claim 3, characterized in that: The hydrogen bond donor-choline halide-lithium halide is obtained by mixing the hydrogen bond donor, choline halide and lithium halide at 70-90°C.
5. The method for preparing the porous carbon negative electrode material according to claim 4, characterized in that: The molar ratio of the hydrogen bond donor, the choline halide and the lithium halide is 1:2:
1.
6. The method for preparing a porous carbon negative electrode material according to claim 4, characterized in that: The hydrogen bond donor is selected from at least one of oxalic acid and glycerol.
7. The method for preparing a porous carbon negative electrode material according to claim 4, characterized in that: The choline halide is selected from at least one of choline fluoride, choline chloride and choline bromide.
8. The method for preparing a porous carbon negative electrode material according to claim 4, characterized in that: The lithium halide is selected from at least one of lithium fluoride, lithium chloride and lithium bromide.
9. A porous carbon negative electrode material, characterized in that: The porous carbon negative electrode material is prepared by the method for preparing the porous carbon negative electrode material as described in any one of claims 1 to 8.
10. A lithium ion battery, characterized in that: Comprising the porous carbon negative electrode material as claimed in claim 9.
Citation Information
Patent Citations
Carbon-coated lithium manganese phosphate cathode material and preparation method thereof
CN105720253A
Carbon-nitrogen-lithium multi-phase doped lithium ion battery negative electrode material, preparation method of material, lithium ion battery negative electrode plate and lithium ion battery
CN109888181A
Eutectic solvent as well as preparation method and application thereof
CN115926203A
High-performance biomass derived hard carbon negative electrode material as well as preparation method and application thereof
CN117049509A
Process for the production of mesoporous activated carbon
DE102020105236A1
Cited By
Microwave-assisted activation-free method for preparing asphalt-based porous carbon
CN120288767A
Method for preparing CMS carbon molecular sieve from flower mud recovery waste and application of CMS carbon molecular sieve
CN121361792A